2011
DOI: 10.1007/s13353-011-0049-x
|View full text |Cite
|
Sign up to set email alerts
|

DArT markers tightly linked with the Rfc1 gene controlling restoration of male fertility in the CMS-C system in cultivated rye (Secale cereale L.)

Abstract: The Rfc1 gene controls restoration of male fertility in rye (Secale cereale L.) with sterility-inducing cytoplasm CMS-C. Two populations of recombinant inbred lines (RIL) were used in this study to identify DArT markers located on the 4RL chromosome, in the close vicinity of the Rfc1 gene. In the population developed from the 541×2020LM intercross, numerous markers tightly linked with the restorer gene were identified. This group contained 91 DArT markers and three SCARs additionally analyzed in the study. All… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
25
0
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 26 publications
(28 citation statements)
references
References 11 publications
2
25
0
1
Order By: Relevance
“…The first high-throughput genotyping technology was established for rye in 2009 with the development of a 1520-clone DArT genotyping panel (Bolibok-Bragoszewska et al, 2009). Since then, it was successfully applied for high density genetic map construction, both in rye and triticale (Bolibok-Bragoszewska et al, 2009; Milczarski et al, 2011; Tyrka et al, 2011, 2015), genome-wide germplasm characterization (Bolibok-Bragoszewska et al, 2014), QTL/gene mapping (Stojałowski et al, 2011; Miedaner et al, 2012; Myśków et al, 2012; Milczarski et al, 2016), and genomic selection (Wang et al, 2014, 2015; Schulthess et al, 2015). Following transcriptome sequencing a Rye5K SNP genotyping panel was developed and used for construction of high density transcript map (Haseneyer et al, 2011; Martis et al, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…The first high-throughput genotyping technology was established for rye in 2009 with the development of a 1520-clone DArT genotyping panel (Bolibok-Bragoszewska et al, 2009). Since then, it was successfully applied for high density genetic map construction, both in rye and triticale (Bolibok-Bragoszewska et al, 2009; Milczarski et al, 2011; Tyrka et al, 2011, 2015), genome-wide germplasm characterization (Bolibok-Bragoszewska et al, 2014), QTL/gene mapping (Stojałowski et al, 2011; Miedaner et al, 2012; Myśków et al, 2012; Milczarski et al, 2016), and genomic selection (Wang et al, 2014, 2015; Schulthess et al, 2015). Following transcriptome sequencing a Rye5K SNP genotyping panel was developed and used for construction of high density transcript map (Haseneyer et al, 2011; Martis et al, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…In successful hybrid breeding, one of the most important factors is the careful choice of parental components displaying a high combining ability strictly associated with their genetic distance (GD). It was demonstrated that molecular markers can also be useful for identification of rye cytoplasmic male sterility forms and Rfc genes (Stojałowski et al, 2011). The relationship between the heterosis effect of particular traits and the GD of parental forms has been studied in wheat (Dreisigacker et al, 2005;Krystkowiak et al, 2009;Zhao et al, 2013), barley (Hordeum vulgare L.; Zhong et al, 2009), maize (Zea mays L.; Riedelsheimer et al, 2012;Windhausen et al, 2012), and rice (Oryza sativa L.; Xu et al, 2014).…”
mentioning
confidence: 99%
“…, Stojałowski et al. ). This could point to a single origin of the Rf mutation in Southwest Asia, the region where rye evolved.…”
Section: Discussionmentioning
confidence: 99%
“…, Stojałowski et al. ) was linked to the same marker loci as the three Rfp genes mentioned. The Rfp gene from IRAN IX has been extensively used in practical breeding with the cultivar ‘Pollino’ (listed in 2005) being the first of a series of hybrids with superior male‐fertility restoration.…”
mentioning
confidence: 99%